2015
DOI: 10.1371/journal.pone.0129867
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tolerogenic Dendritic Cells by a PEGylated TLR7 Ligand for Treatment of Type 1 Diabetes

Abstract: Autoimmune diabetes mellitus (DM) results from the destruction of pancreatic islet cells by activated T lymphocytes, which have been primed by activated dendritic cells (DC). Individualized therapy with ex vivo DC manipulation and reinfusion has been proposed as a treatment for DM, but this treatment is limited by cost, and requires specialized facilities. A means of in situ modulation of the DC phenotype in the host would be more accessible. Here we report a novel innate immune modulator, 1Z1, generated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 57 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…PD-L1 is a ligand for the negative costimulatory molecule PD-1, and this signaling pathway has been shown to compromise functions of Ag-specific T cells (61). Through upregulation of PD-L1, IFN-g leads to induction of tolerogenic properties in DCs (43,58), which acquire the capability to effectively suppress T cell responses in a PD-L1/PD-1-dependent manner (42,62,63). Furthermore, the ability of IL-27 as an inducer of tolerogenic DCs was recently confirmed in a clinical study in chronic obstructive pulmonary disease that provided evidence that IL-27-exposed DCs induced regulatory T cells in obstructive pulmonary disease patients (64).…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is a ligand for the negative costimulatory molecule PD-1, and this signaling pathway has been shown to compromise functions of Ag-specific T cells (61). Through upregulation of PD-L1, IFN-g leads to induction of tolerogenic properties in DCs (43,58), which acquire the capability to effectively suppress T cell responses in a PD-L1/PD-1-dependent manner (42,62,63). Furthermore, the ability of IL-27 as an inducer of tolerogenic DCs was recently confirmed in a clinical study in chronic obstructive pulmonary disease that provided evidence that IL-27-exposed DCs induced regulatory T cells in obstructive pulmonary disease patients (64).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated from SCC7, MEER, and RAW264.7 murine macrophage cells using RNeasy Plus kit (QIAGEN) and was reverse-transcribed using iScript (Bio-Rad). qPCR analyses using Taqman Gene Expression Assay (Thermo Fisher Scientific) were performed by CFX-Connect Real-Time System (Bio-Rad) as described previously (76). Primers purchased from Thermo Fisher Scientific are described in Supplemental Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…To test that our protocol for generating tolDCs led to diabetes prevention in vivo, tolDCs were generated from bone marrow cells of NOD mice by using dexamethasone and vitamin D 2 . Previous studies showed that to prevent diabetes onset and induce Agspecific tolerance in animal model of diabetes, Ag supply might not be required in DC-based therapies for T1D (31)(32)(33)(34). It is suggested that unpulsed DCs could pick up diabetogenic Ags in vivo and present them in a tolerogenic fashion (35).…”
Section: Dexamethasone/vitamin D 2 -Modulated Nod Dcs Delayed Diabetementioning
confidence: 99%